Reviewing the state of the art of probiotics as clinical modalities for brain–gut–microbiota axis associated disorders - Wiegers, Cato; Veerman, Mariët A.; Brummer, Robert Jan; Larsen, Olaf F. A. (Frontiers in Microbiology, 2022)
The rise in prevalence of mental and neurological disorders is causing a high burden on society, however adequate interventions are not always available. The brain-gut-microbiota axis (BGMA) may provide a new angle for the development of clinical modalities. Due to the intricate bi-directional signalling between the brain and the gut, it may be helpful to look into interventions that target the gut, such as probiotics. Therefore, this review aimed to investigate the state of the art of probiotics and their potential as clinical modalities for BGMA-associated indications by gaining insight into patents and clinical trials that have been applied for and executed since 1999. A total of 565 patents and 390 clinical trials were found, focusing on probiotic applications for 83 indications. Since the start of the 21st century, the highest numbers of patents and clinical trials were related to primary neuropsychological, affective (depression, anxiety) and cognitive disorders, neurodegenerative and/or inflammatory brain disorders (Alzheimer’s disease, Parkinson’s disease, amongst others), and gastrointestinal disorders (irritable bowel syndrome). The locations where the most patents and clinical trials were registered included China, the US and Iran. From 1999 to ~2013 a slight growth could be seen in the numbers of patents and clinical trials, followed by an almost exponential growth from ~2013 onwards. Overall, the developments of the state of the art were in accordance with previous research, however it appeared that clinical trials showed a slightly slower growth compared to patents, which may have implications for the future implementation of probiotics as clinical modalities for BGMA-associated indications.